ANALYSIS OF THE CURRENT STATE OF DEVELOPMENT OF SMALL AND MEDIUM-SIZED BUSINESSES IN UKRAINE IN THE CONTEXT OF THE MILITARY SITUATION - Olha K. Nezghoda (Êvropejsʹkij Vektor Ekonomìčnogo Rozvitku, 2023)
The article examines the consequences of the impact of Russia’s military aggression on the current state of small and medium-sized enterprises (SMEs) in Ukraine. One of the priority areas for the recovery of the Ukrainian economy from the consequences of the economic crisis caused by military actions and the global crisis is the development of small and medium-sized enterprises. Therefore, the purpose of the article is to analyse the dynamics of business activity of small and medium-sized businesses within the domestic market and foreign economic activity, considering the tax reform that has begun since the Russian Federation invaded Ukraine. The subject of the study was chosen to be Ukraine’s small and medium-sized businesses for several reasons: firstly, SMEs accounted for about 70% of employment in the country; secondly, SMEs accounted for almost 60% of gross sales before the military situation. The study used theoretical and empirical methods: induction, explanation, generalisation, comparative analysis, observation and description, and the abstract logical approach was used to make conclusions. In our study, we took into account legislative changes and existing government support instruments that contribute to improving the business climate in the country and, based on secondary data, identified how the mood of entrepreneurs has changed and what the Ukrainian business community should expect shortly, taking into account the reforms and the current economic situation in Ukraine. In addition, the study paid particular attention to the assessments of business representatives, primarily to the expectations of industrial enterprises regarding the prospects for developing their business activity, as expressed in the business confidence indicator and the business climate indicator. The paper has identified several problems that hinder the functioning of SMEs by industry and identified several scenarios for developing SME business needs, taking into account current government actions. The main challenges to the development of SMEs were logistical problems, labour shortages, a significant rise in the cost of raw materials and resources for production, risks associated with hostilities and mining, blocking of foreign trade flows, forced relocation, etc. In the face of these challenges, SMEs are trying to adapt by focusing on business processes, building new development strategies, and becoming flexible. However, a significant proportion of Ukrainian SMEs have been forced to refocus on export development due to the decline in the purchasing power of citizens.